The Attitudinal Commitment Of Contractors For Site Environmental Practices In Malaysia - Yahaya, Izyan (2017)
Direct involvement of contractors at construction site positioned them as the main party to influence the project environmental performance. However, the increasing concern of environmental issues at construction site indicated that commitment on this aspect need to be fortified. As the contractor firms consist of Top Management (TM) and Site Management (SM), their synchronized commitment is vital to strengthen their action towards environmental protection. This study aims to develop a framework of the contractors’ Attitudinal Commitment for Site Environmental Practices (SEPs) through the attainment of four research objectives, i.e. exploring the level of SEPs, assessing the Attitudinal Commitment of TM and SM, investigating the factors influencing the Attitudinal Commitment and demonstrating the connection of Attitudinal Commitment between the TM and SM. Two phases of investigations, i.e. (QUAN-QUAL) were employed in order to obtain more conclusive and comprehensive findings. In Phase 1, the level of SEPs implementation are explored and the Attitudinal Commitment of TM and SM are assessed. Through random sampling, a total of 194 responses were obtained from construction firms of grade G1-G7 from Peninsular Malaysia. Phase 2 involved interviews with 16 TM and SM from G7 firms that are identified through selective sampling.